No Choice But to Look Elsewhere:: Attracting Immigrants to Newfoundland, 1840-1890 - Lambert, Carolyn (Acadiensis, 2012)
Nineteenth-century Newfoundland was caught up in North America’s drive towards progress. The desire for landward development was present within political discourse from the 1840s onwards, politicians arguing that economic diversification – particularly agricultural development – would free the population from coastal resource dependency. Failure to entice fishermen to farm led officials to believe that individuals to push Newfoundland forward would have to be found elsewhere. Contemporaries were aware of the geographic limitations preventing large-scale immigration, and hoped for a small number of skilled agriculturalists from the British Isles. Yet no government formulated a formal immigration policy, and proposed immigration strategies were cautious.